How do Teachers Enhance Elementary School Students’ Numeracy Through the Integration of Singing and Jarimatika Methods? - Novitasari, Welly; Herwin (LPPM Press, 2023)
This research aims to reveal teachers' efforts to improve the numeracy of lower grade elementary school students using singing and Jarimatika methods. This research is a type of qualitative research with a case study approach. Research data was collected from elementary school teachers and low-grade elementary school students using observation and interviews. The results of the research show that the teacher's efforts to integrate the singing and Jarimatika methods were carried out using the song